Revisiting the UK Genetic Severity Score for NF2: a proposal for the addition of a functional genetic component. Issue 7 (4th August 2021) - Catasús, Núria; Garcia, Belen; Galván-Femenía, Iván; Plana, Adrià; Negro, Alejandro; Rosas, Inma; Ros, Andrea; Amilibia, Emilio; Becerra, Juan Luis; Hostalot, Cristina; Rocaribas, Francesc; Bielsa, Isabel; et al.
Abstract : Background: Neurofibromatosis type 2 (NF2) is an autosomal dominant disorder characterised by the development of multiple schwannomas, especially on vestibular nerves, and meningiomas. The UK NF2 Genetic Severity Score (GSS) is useful to predict the progression of the disease from germline NF2 pathogenic variants, which allows the clinical follow-up and the genetic counselling offered to affected families to be optimised. Methods: 52 Spanish patients were classified using the GSS, and patients' clinical severity was measured and compared between GSS groups. The GSS was reviewed with the addition of phenotype quantification, genetic variant classification and functional assays of Merlin and its downstream pathways. Principal component analysis and regression models were used to evaluate the differences between severity and the effect of NF2 germline variants. Results: The GSS was validated in the Spanish NF2 cohort. However, for 25% of mosaic patients and patients harbouring variants associated with mild and moderate phenotypes, it did not perform as well for predicting clinical outcomes as it did for pathogenic variants associated with severe phenotypes. We studied the possibility of modifying the mutation classification in the GSS by adding the impact of pathogenic variants on the function of Merlin in 27 cases. This revision helped to reduce variability within NF2 mutation classes and moderately enhanced the correlation between patient phenotype and the different prognosis parameters analysed (R 2 =0.38 vs R 2 =0.32, p>0001). Conclusions: We validated the UK NF2 GSS in a Spanish NF2 cohort, despite the significant phenotypic variability identified within it. The revision of the GSS, named Functional Genetic Severity Score, could add value for the classification of mosaic patients and patients showing mild and moderate phenotypes once it has been validated in other cohorts.